SECTION LAUNDRY PERFORMANCE IN GRAND JATRA HOTEL PEKANBARU - Filda Fransisca; Teguh Widodo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at the Grand Jatra Hotel Pekanbaru, the purpose of this study was to determine the performance carried out by the laundry section in Grand Jatra Hotel Pekanbaru City. The sample in this study was 94 respondents, data analysis in this study was quantitative by using a hypothesis test (t test and coefficient of determination). Based on the results of the analysis using the SPSS program it is proven that together the ability, motivation and opportunity factors greatly influence the performance of the laundry section. This is evidenced by the ability variable with a T count of 3,115 (>) from T table 1.99, motivation variable with T count 3.656 (>) from T table 1.99, opportunity variable with T count 2.510 (>) from T table 1.99. Simultaneously the factors consisting of 3 variables as explained in the framework of thinking in this study, where the independent variables significantly influence the performance of the laundry section at the Grand Jatra Hotel Pekanbaru. R value of 0.849, means the closeness relationship together between the dependent variable and the independent variable is very good because R is between 0.80-1,000. Adjusted R Square value of 0.701, which means 70.1% of the ability, motivation and opportunity variables that affect the performance of the laundry section in the grand Jatra Hotel Pekanbaru, while the rest (100% -70.1% = 29.9%) is influenced by other causes not examined in this study.Keywords: Performance, Laundry Section, Grand Jatra Hotel, Pekanbaru City